Svet v nenehnem primežu varnostne dileme - Bučar, Bojko (Teorija in praksa, 2025)
The article contributes to discussions on security in international relations. A departure is made from focusing on the conceptual and historical contexts of processes and developments in the contemporary international community. Through historical and causal analyses, the phenomenon of solving security issues as part of modern developments in international relations is explored. In the second part, more recent developments in theory are presented, together with the security dilemma as a structural element of the development of societies, and the state and international system where focus is given to the security dilemma of actors. At the end, the article deals with the challenges of contemporary security and issues as they pertain to Slovenia.
Keywords: international security; Mednarodna skupnost; mednarodna varnost; Nacionalna varnost; new world order; nova svetovna ureditev; security; security dilemma; varnost; varnostna dilema